AJUSTE DO MODELO ADAPTATIVO DE VESTIMENTA CONSIDERADO NO ÍNDICE CLIMÁTICO TÉRMICO UNIVERSAL (UTCI) PARA CLIMA TROPICAL DE SAVANA - Borges, Vera Cristina de Arêa; Callejas, Ivan Júlio Apolônio; Durante, Luciane Cleonice (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Universal Thermal Climate Index (UTCI) was design to provide a measure of human thermal perception in all regions of the planet, despite its clothing thermal isolation model be derived considering the adaptive behavior of the European population. The adjustment model is integrated with the UTCI thermoregulation model and it relates clothing thermal insulation (Icl) as function of the air temperature (Ta). This work aims to analyze the clotting thermal isolation behavior (Icl) observed for the tropical climate population in relation to the one imputed in the UTCI index. 685 passers-by were interviewed in the city of Cuiabá-MT/ Brazil (tropical savanna climate Aw) during hot-dry and hot-humid weather conditions. It was used the Loess Local Regression statistical technique to derive the clothing thermal model isolation observed in field. The results demonstrated thermal isolation required by residents was lower than the model derived for European population for the air temperatures below 25°C, which contradicted the initial hypothesis of the survey that populations being more adapted to high air temperatures would require greater clothing thermal isolation than the Europeans. Further field campaigns need to be conducted to confirm the necessity of developing specific clothing thermal model isolation for the population that resides in a tropical climate.